A physiological comparison of three techniques for reviving sockeye salmon exposed to a severe capture stressor during upriver migration. (21st April 2015) - Raby, Graham D.; Wilson, Samantha M.; Patterson, David A.; Hinch, Scott G.; Clark, Timothy D.; Farrell, Anthony P.; Cooke, Steven J.
Abstract : We used physiological measurements to compare different methods for reviving salmon after a severe capture stressor that involved 3 min of air exposure. Both a powered recovery box and a flow-through in-river recovery bag enabled revival, but prolonged confinement appeared to act as an additional stressor. Abstract : Capture of fish in commercial and recreational fisheries causes disruption to their physiological homeostasis and can result in delayed mortality for fish that are released. For fish that are severely impaired, it may be desirable to attempt revival prior to release to reduce the likelihood of post-release mortality. In this study, male sockeye salmon ( Oncorhynchus nerka ) undergoing their upriver migration were used to examine short-term physiological changes during the following three revival treatments after beach seine capture and air exposure: a pump-powered recovery box that provided ram ventilation at one of two water flow rates; and a cylindrical, in-river recovery bag, which ensured that fish were oriented into the river flow. Beach seine capture followed by a 3 min air exposure resulted in severe impairment of reflexes such that fish could not maintain positive orientation or properly ventilate. All three revival treatments resulted in significant reductions in reflex impairment within 15 min, with full recovery of reflex responses observed within 60–120 min. For most variables measured, including plasma lactate, cortisol and osmolality, there were no significant differences among revival treatments. There was some evidence for impaired recovery in the low-flow recovery box, in the form of higher haematocrit and plasma sodium. These data mirror published recovery profiles for a recovery box study in the marine environment where a survival benefit occurred, suggesting that the methods tested here are viable options for reviving salmon caught in freshwater. Importantly, with most of the benefit to animal vitality accrued in the first 15 min, prolonging recovery when fish become vigorous may not provide added benefit because the confinement itself is likely to serve as a stressor.